Influence of Substrate Composition and Container Size on the Growth of Tissue Culture Propagated Apple Rootstock Plants - Jae Kyung Kim; Md. Rayhan Ahmed Shawon; Jin Hee An; Yeo Jong Yun; Soo Jeong Park; Jong Kuk Na; Ki Young Choi (Agronomy, 2021)
Substrate composition and container size are considered crucial for apple rootstock grown in a plug seedling system. This study investigated the effect of substrate material’s proportion and different container volumes on the growth of apple rootstock (M-9) plants propagated by tissue culture. In substrate composition, three different ratios of peat moss (PM): vermiculite (VL): perlite (PL) at 1:1:1 (S1), 1:2:3 (S2), 3:1:2 (S3) were used. For container size, plants were grown in 1000 mL (C1), 500 mL (C2), and 300 mL (C3) containers filled by 1:1:1 mixture of PM, VL and PL. In both cases, plants were treated eleven weeks in a green house. Our results demonstrate that the plant height, number of leaves, leaf area, shoot fresh weight and root fresh weight of apple rootstock were significantly higher in substrate composition S3 compared with S1 composition. However, chlorophyll content (SPAD) and photosynthesis rate were unaffected by variation of substrate composition. Furthermore, rootstock grown in C1 container showed plant height, number of leaves, leaf area, number of nodes, root length, shoot and root’s fresh and dry weight were significantly higher than those grown in C2 and C3 volume containers. The chlorophyll content and transpiration rate were not significantly affected by the different container volumes. These results suggest that the substrate ratio 3:1:2 of PM:VL:PL and container size 1000 mL were more favorable than other treatments for initial growth and development of the tissue culture propagated apple rootstock plants.